Assistance in Training Business Strategy Model Canvas in Sambal Pecel UD Business Distra Adjie Madiun City - Asfahani, Asfahani; Kirom, Ahmad; Iqbal, Khurshed (International Assulta of Research and Engagement (IARE), 2024)
This article examines the implementation of Business Model Canvas (BMC) strategy training in the UD Distra Adjie Pecel business in Madiun City. The purpose of this community service is to discuss the challenges faced by UD Distra Adjie such as marketing difficulties and fluctuating business performance, and to propose BMC training to optimize its business strategy. This community service method uses the Asset Based Community Development (ABCD) approach. This training empowers UD Distra Adjie business actors by utilizing their assets and resources. The training includes interactive workshops, strategic planning, and ongoing monitoring and evaluation to ensure practical implementation and sustainability. The results of the community service show a significant increase in strategic understanding, business model development, and competitive position. Participants actively participate in the BMC process, which leads to increased creativity, innovation, and economic empowerment. The study results conclude that BMC training improves individual business performance and positively contributes to the regional economy by fostering a stronger entrepreneurial environment.